The analysis of research methods and results on resistance of nickel-titanium endodontic instruments to torsion load: the systematic review - D. S. Shirokova; Z. S. Khabadze; D. V. Voskresenskaya; F. R. Ismailov; Z. M. Gasanova; N. N. Fedotova (LLC "Endo Press", 2021)
Relevance. The objective of this study was to analyze current data concerning research methods and results on resistance of nickel-titanium endodontic instruments to torsion load in order to minimize complications of dental root canal treatment. The use of the nickel -titanium endodontic instruments is a special importance to ensure high-quality dental root canal treatment; it prevents the further contamination of the canals with microorganisms. However, these instruments can form a fracture under torsional load which leads to further complications.Aim. The analysis of research methods and results on resistance of nickel-titanium endodontic instruments to torsion load for minimization complications.Materials and methods. A series of publications in the electronic databases such as Google Scholar, Pub Med was analyzed in the course of a systematic review of the literature. The articles dealing with nickel-titanium endodontic instruments and torsion load that directly influences the quality of dental root canal treatment were included in the paper.Results. 73 articles were viewed during the review. Having analyzed the literature for inclusion criteria, the total number of publications has become 51. There were 16 main methods which demonstrated the influence of torsion load on endodontic instruments. These methods were summarized in the Table 1.Conclusions. As regards literature data, there are a various number of methods which converge to one conclusion: nickel-titanium instruments cannot fully resist torsion load. Fracture is caused approximately in 0,5-5% of cases.